THE POLITICS OF IDENTITY IN REVOLUTIONARY CHINA BEFORE AND AFTER 1949: THE CASE OF WEI BAQUN. (January 2015) - H, X
Abstract : Wei Baqun, leader of the influential Donglan Peasant Movement in southern China in the 1920s and 1930s, was attacked by his Nationalist enemies as a real and dangerous Communist long before he joined the Chinese Communist Party. Meanwhile, some of his Communist comrades were reluctant to admit him into the Party or to recognize him as a genuine Communist even after he joined the Communist Party. But after his death, they all began to promote him as a perfect Communist. Through an analysis of Wei Baqun's life and revolution, this article shows how controversial and conflicting perceptions of the political identity of a political leader could exert strong influence on the political career of the leader and on local and national politics in revolutionary China. The article also attempts to explain why the confusion and controversy over Wei Baqun's identity dissipated after his death.